Electrospinning preparation and electromagnetic wave absorption properties of SiCN fibers. Issue 8 (1st June 2020) - Xiao, Feifei; Sun, Haibin; Li, Jiao; Guo, Xue; Zhang, Hua; Lu, Junbin; Pan, Zhaoxu; Xu, Jiakun
Abstract: The SiCN fibers were synthesized by the combination of polymer-derived method and electrospinning technology. The XRD, FT-IR, TEM, SEM, XPS and Raman spectroscopy were applied to study the phase composition, chemical structure, morphology and carbon crystalline state of the SiCN fibers. In addition, a vector network analyzer was used to study the electromagnetic properties of SiCN fibers. The results showed the amorphous carbon increased with the temperature increasing, which can significantly adjust the dielectric properties of the SiCN fibers. The SiCN fibers synthesized at 1300 °C showed excellent electromagnetic wave (EMW) absorption performance, wherein the effective absorption bandwidth was 4.59 GHz (11.8~16.4 GHz, RL < -10 dB) and the RLmin value reached −31.1 dB at the thickness of 2 mm.